Engineering in vitro vascular microsystems - Qiao Liu; Guoliang Ying; Chenyan Hu; Lingyu Du; Huaiyi Zhang; Zhenye Wang; Hongyan Yue; Ali K. Yetisen; Guixue Wang; Yang Shen; Nan Jiang (Microsystems & Nanoengineering)
Abstract Blood vessels are hierarchical microchannels that transport nutrients and oxygen to different tissues and organs, while also eliminating metabolic waste from the body. Disorders of the vascular system impact both physiological and pathological processes. Conventional animal vascular models are complex, high-cost, time-consuming, and low-validity, which have limited the exploration of effective in vitro vascular microsystems. The morphologies of micro-scaled tubular structures and physiological properties of vascular tissues, including mechanical strength, thrombogenicity, and immunogenicity, can be mimicked in vitro by engineering strategies. This review highlights the state-of-the-art and advanced engineering strategies for in vitro vascular microsystems, covering the domains related to rational designs, manufacturing approaches, supporting materials, and organ-specific cell types. A broad range of biomedical applications of in vitro vascular microsystems are also summarized, including the recent advances in engineered vascularized tissues and organs for physiological and pathological study, drug screening, and personalized medicine. Moreover, the commercialization of in vitro vascular microsystems, the feasibility and limitations of current strategies and commercially available products, as well as perspectives on future directions for exploration, are elaborated. The in vitro modeling of vascular microsystems will facilitate rapid, robust, and efficient analysis in tissue engineering and broader regenerative medicine towards the development of personalized treatment approaches.